Development of Children Under 5 Years of Age Living on Landfill Sites and Their Environmental Sanitation Conditions - Kadek Ayu Erika; Aprilia Dwi Aryanti; Suni Hariati (Indonesian Journal of Global Health Research, 2024)
Less than optimal development of children under 5 years of age can be caused by one factor inadequate environmental sanitation, especially in landfill sites. Objective to determine the development of children under 5 years of age and the environmental sanitation of those living in landfill sites. Method: This research uses descriptive analytics with a purposive sampling technique. The number of samples in this study was 91 parents with children under 5 years of age in landfill sites. Assessment of development using the Developmental Pre-Screening Questionnaire and environmental sanitation through interviews and observations. Data were presented in frequency distributions of demographic characteristics, development of children under 5 years of age, environmental sanitation, and cross-tabulations. This study showed the interpretation of the development of children under 5 years of age who were in landfill sites was development according to age (90.3%) at pre-school age, doubtful (38.1%) and there was a possibility of deviation (57.1%) at infant age. Environmental sanitation conditions in the landfill sites consisted of drinking water sources from boreholes/pumps (27.5%); available, watertight, and uncovered waste bins (51.6%); use of septic tank (100%); and no sewerage available (49.5%). The parents who use borehole/pump water sources, trash bins that are not watertight and uncovered, and no sewerage in the landfill sites where parents live, have the results of the interpretation that children under 5 years of age develop doubtful and there is a possibility of deviation. Therefore, the important role of nurses in providing education and early stimulation of children under 5 years of age development by involving parents, optimizing the uses of the Developmental Pre-Screening Questionnaire at public health centers, education and management of a conducive physical environment to support the development and handling of children under 5 years of age who experience delays.